The technical challenge of Functional 18F-FDG-PET Brain imaging in paediatric epilepsy - Mota, AM (2012)
Epilepsy is a chronic brain disease, characterized by the appearance of crisis (whit or without convulsions), caused by abnormal electric activity on brain cells. Neuroimaging might be necessary in the work-up of epilepsy for localisation of the seizure focus for possible surgical cure. In our department, we started performing inter-ictal 18F-2-deoxyglucose (FDG)-PET/TC Brain imaging in 2009, in paediatric patients, following EANM procedure guidelines. Aim: the aim of the study was to retrospectively review all the performed inter-ictal 18F-FDG-PET/TC brain imaging, to assess the difficulties found during these procedures and the deviation according to guideline recommendations. We also intend to focus on the major importance of an optimal cooperation with other departments, such as anaesthesiology and neurophysiology. Material and Methods: between 2009 and 2012, eleven patients (pt) were referred for an 18F-FDG-PET-TC brain study, with ages between 10 months - 18 years old all with medically intractable epilepsy. The exams were performed with different conditions according to the needs of each patient, because we know that exceptional procedures call for special conditions. Results: All files were review for pt information pertinent to performance of the procedure, pt pre-arrival preparation, pt pre-injection preparation, pt monitoring for ictal crises before injection (EEG), pt sedation, variability of radiopharmaceutical administration and data acquisition parameters. 8 of the pt were performed with anaesthesia while 3 without since the pediatric patient were cooperative. All of the pt were monitored under parental surveillance, one with additional movie recording and other with EEG. Conclusion: We found that this process of retrospective review of this pool of paediatric patients with epilepsy enhanced the learning curve in this very specific procedure. We also found it critical to request the collaboration of the departments of anaesthesiology and neurophysiology.